Peran Kepolisian dalam Menjaga Stabilitas Keamanan Selama Penerapan Kebijakan PSBB - THOMAS AGUNG KURNIANTO (Sekolah Tinggi Ilmu Kepolisian, 2021)
Abstract The decision to enact Large-Scale Social Restrictions (PSBB) is a policy choice taken by the government to prevent the spread and transmission of the Covid-19 virus since it was declared a pandemic by WHO. The PSBB policy has had a significant impact on the economic sector. The community has difficulty getting their needs, as a result of restrictions on activities carried out by the government. This has consequences for the high number of crimes during the pandemic. The POLRI institution, which is authorized by law to maintain national security, takes strategic steps to secure the implementation of PSSB activities and maintain the stability of national security. Strategic steps taken include: issuing various regulations related to safeguarding the implementation of PSBB policies, including the issuance of the Chief of Police’s Declaration and the formation of a task force to take action against various crimes, both conventional crimes, economic crimes and cyber crimes during the Covid-19 pandemic. Keywords: PSBB’s Policies; National Security Stability; Covid-19; POLRI. Abstrak Keputusan pemberlakuan Pembatasan Sosial Berskala Besar (PSBB) merupakan pilihan kebijakan yang diambil pemerintah dalam rangka mencegah penyebaran dan penularan virus Covid-19 sejak ditetapkan sebagai pandemi oleh WHO. Kebijakan PSBB membawa dampak yang signifikan pada bidang ekonomi. Masyarakat mengalami kesulitan memenuhi kebutuhan, sebagai akibat pembatasan kegiatan yang dilakukan oleh pemerintah. Hal tersebut membawa konsekuensi pada tingginya angka kejahatan di masa pandemi. Institusi POLRI yang oleh undang-undang diberi kewenangan untuk menjaga keamanan nasional, mengambil langkah strategis untuk mengamankan pelaksanaan kegiatan PSSB serta menjaga stabilitas keamanan nasional. Langkah strategis yang diambil antara lain: mengeluarkan berbagai peraturan terkait pengamanan pelaksanaan kebijakan PSBB, termasuk dengan dikeluarkannya Maklumat Kapolri serta pembentukan satgas untuk menindak berbagai kejahatan, baik kejahatan konvensional, kejahatan bidang ekonomi, dan kejahatan siber di masa pandemi Covid-19. Kata Kunci: PSBB; Kejahatan; Stabilitas Keamanan Nasional; Covid-19; POLRI.